Kajian Laboratorium Kuat Tarik Belah Beton Egg Tray Dengan Penambahan Superplasticizer: Laboratory Study Of Split Tensile Strength Of Egg Tray Concrete With The Addition Of Superplasticizer - Rafael, Jusuf Wilson Meynerd; Lukas, Alva Yuventus (Media Ilmiah Teknik Sipil, 2024)
Using egg tray waste as a fine aggregate substitute can be an alternative for making environmentally friendly concrete. The weaknesses of concrete with egg trays can corrected by adding a superplasticizer to both the compressive strength and split tensile strength of the concrete. This study used an egg tray waste as a fine aggregate substitution of 3% with variations in superplasticizer content. The test specimens were by a concrete cylinder with a diameter of 15 cm and a height of 30 cm, which varied the superplasticizer content by 0%, 0.5%, 1%, 1.5%, 2%, and 5% compared to normal concrete conditions. The test results show that concrete given a 3% egg tray waste as a substitute for fine aggregate has a lower split tensile strength value than normal concrete. Adding superplasticizer material can increase the value of split tensile strength up to 1% superplasticizer content. As the superplasticizer content increases, the value of the split tensile strength will again decrease.